Factors of positive emotion among catering students at UTHM during COVID-19 pandemic - Ahmad Zabidi, Nurul Afiqah; Zakariah, Siti Hajar; Abdul Rahman, Khairul Anuar; Ahmad, Nor Aziah; Tukiran, Nor Anis Intan Aqiah; Syawal Ismail, Lisa Mariam1 (Kolej Komuniti Sungai Siput, 2022)
This study aims to identify the main factors influencing positive emotions among Bachelor of Vocational Education (ISMPV) students catering at UTHM during the COVID-19 pandemic and to identify the differences in positive emotional factors between male and female students. This study only involves catering students from the Faculty of Technical and Vocational Education, Universiti Tun Hussein Onn Malaysia. This group of students is selected because they have experience learning before and during the COVID-19 pandemic. This is a quantitative study; therefore, the survey was conducted using a questionnaire instrument to obtain information from the sample. Analytical methods were used in descriptive and inferential forms, using questionnaires as research instruments. The data obtained were analyzed using the SPSS (Statistical Package for the Social Sciences) software version 25 to obtain the mean values, standard deviations, and t-test to observe the differences between students, male and female. The results showed that the main factor influencing positive emotions among catering students at UTHM during the Covid-19 pandemic was the social support factor with a total mean score of 4.66. In addition, the inferential findings of the t-test found that there was no significant difference in positive emotional factors between male and female students because all the factors involved greatly helped each student to support positive thinking and behavior throughout the learning process.